2018
DOI: 10.1007/s13205-018-1133-2
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of detergent compatible protease from halophilic Virgibacillus sp. CD6

Abstract: A halophilic bacterium, sp. strain CD6, was isolated from salted fish and its extracellular protease was characterized. Protease production was found to be highest when yeast extract was used as nitrogen source for growth. The protease exhibited stability at wide range of salt concentration (0-12.5%, w/v), temperatures (20-60 °C), and pH (4-10) with maximum activity at 10.0% (w/v) NaCl, 60 °C, pH 7 and 10, indicating its polyextremophilicity. The protease activity was enhanced in the presence of Mg, Mn, Cd, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 39 publications
2
15
0
Order By: Relevance
“…The purity and concentration of harvested genomic DNA were checked using a Nanodrop ™ 1000 spectrophotometer and Qubit ® 3.0 fluorometer (Thermoscientific) respectively, which were 2.03 (A 260/280 ) and 820 ng/µl. The 16S rRNA gene of strain CL38 was amplified using primers: 27F (5'-AGAGTTTGATCMTGGCTCAG-'3) and 1525R (5'-AAGGAGGTGWTCCARCC-3') [21] with conditions as stated [22]. [36] and edited using MEGA 7.0.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The purity and concentration of harvested genomic DNA were checked using a Nanodrop ™ 1000 spectrophotometer and Qubit ® 3.0 fluorometer (Thermoscientific) respectively, which were 2.03 (A 260/280 ) and 820 ng/µl. The 16S rRNA gene of strain CL38 was amplified using primers: 27F (5'-AGAGTTTGATCMTGGCTCAG-'3) and 1525R (5'-AAGGAGGTGWTCCARCC-3') [21] with conditions as stated [22]. [36] and edited using MEGA 7.0.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The classical example of industrial application of proteases is for cleaning purposes like detergent additive, contact lens cleaning solution component, etc. (Salwan and Sharma 2019 ; Singh and Bajaj 2017 ; Lam et al 2018 ). The textile industry makes use of proteases for a variety of purposes ranging from degumming of silk, biopolishing of wool in a very much sustainable and eco-friendly approach (Chatha et al 2017 ; Mamo and Assefa 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Ramkumar et al observed more than 91% residual activity of alkaline protease from B. licheniformis NK with Arial followed by Bahar, Tide and Bonux at 1 mg/mL concentration of commercial detergents [95]. Many researchers have diluted the commercial detergents at 7 mg/mL concentration and then used in the compatibility assay [96,97,98,99]; however, we have used 10 mg/mL concentration of detergent solutions and recorded almost similar type of results, this could suggest the tolerance of P1 protease at elevated concentrations of detergents. Therefore, P1 protease could be used as an excellent bio-additive to the detergents.…”
Section: Residual Activity (%)mentioning
confidence: 99%